Coursebook Evaluation and Critical Thinking Integration: A Study of Two Indonesian EYL Textbooks - Wawan Setiawan (Linguapedia, 2025)
This study evaluated two English coursebooks used in Indonesian junior high schools: English for Nusantara, used at SMPN 4 Cikupa Tangerang, and New Frontiers 1, an international coursebook adopted by SMP IT Laa Tahzan Citra Tangerang. The evaluation focused on the quality of the coursebooks in supporting language learning and teaching, and the integration of critical thinking skills. Using a qualitative descriptive research design with a content analysis, data were drawn from Units 1–3, totaling 54 tasks in English for Nusantara and 94 tasks in New Frontiers 1. Findings show that English for Nusantara aligns well with national curriculum goals and provides localized, culturally relevant content. However, it offers limited teacher support resources, minimal pronunciation coverage, and focuses heavily on lower-order skills, with interpretation and explanation making up 56% of tasks. In contrast, New Frontiers 1 demonstrates stronger communicative and task-based features, comprehensive support materials, and greater integration of critical thinking skills, including evaluation (11%) and combined skills (7%). These results highlight the need for future coursebook development in Indonesia to balance local cultural relevance with critical thinking and 21st century competencies, preparing learners for both national and global communication demands.